Markets where buyers also are sellers. How realized home equity may work as an accelerator of house prices - Erling Røed Larsen (Statistics Norway, Research Department, 2010)
The house price level is a function of buyers' realized home equity, and buyers' realized home equity is a function of the house price level. This interdependence follows from the fact that buyers are sellers in the same market. This article examines under what conditions this leads to a possible upward-sloping demand curve with a potentially unstable equilibrium. I employ a parsimonious model with two kinds of buyers, and utilize an augmented Slusky-equation that decomposes Walrasian demand into a substitution, an income, and an endowment income effect. The model demonstrates that instability may occur if first-time buyers' demand is sufficiently inelastic, leverage is stretched, debt-financing is common, and nth-time buyers are relatively more frequent than first-time buyers. Regulation on leverage and a capital gains tax reduce the likelihood of upward-sloping demand. The article utilizes new data from Norway to examine an empirical indicator of an equity accelerator of house prices and finds that over the period 2000-2008 the value of all housing transactions exceeded the aggregate net growth of mortgages by 50%, indicating substantial equity financing. In one year, 2008, the value of aggregate housing transactions was double the growth in net mortgages.
Keywords: D03; D10; D53; E21; E44; G12; R21; R31; 330; capital gains; consumer behavior; endowment income; feedback system; financial acceleration; home equity; housing; instability; interdependence